STUDENTS' RESPONSES TO THE IMPLEMENTATION OF FUN ENGLISH LEARNING STRATEGIES AT SMP IT DARURRAHMAN MAKASSAR - Hidayah, Nur; Atmowardoyo, Haryanto; Ariyani, Amra (Universitas Negeri Makassar, 2024)
This research aims to explore students' responses to using fun English learning strategies at the junior high school level. The method used in this research is field note observation and interviews with students to determine their perceptions regarding the effectiveness and attractiveness of this learning method. The findings of this research indicate that the majority of students gave positive responses to the fun learning approach. They feel more motivated and actively involved and enjoy the interactive and varied learning process. Students report that this method helps them remember new vocabulary more easily and understand English concepts better. However, some students acknowledged the challenges of retaining learned knowledge over the long term without adequate extension. Creative and innovative teachers play an important role in the success of this method, with interesting and interactive teaching variations. In conclusion, the Fun English Learning Strategy proved to be effective in increasing students' motivation and engagement in English learning, although additional strategies are needed to ensure better knowledge retention. This research provides insight for educators and researchers in developing more effective and enjoyable English teaching methods in the future.